A low dose of lysergic acid diethylamide decreases pain perception in healthy volunteers. (April 2021) - Ramaekers, Johannes G; Hutten, Nadia; Mason, Natasha L; Dolder, Patrick; Theunissen, Eef L; Holze, Friederike; Liechti, Matthias E; Feilding, Amanda; Kuypers, Kim PC
Background: Lysergic acid diethylamide (LSD) is an ergot alkaloid derivative with psychedelic properties that has been implicated in the management of persistent pain. Clinical studies in the 1960s and 1970s have demonstrated profound analgesic effects of full doses of LSD in terminally ill patients, but this line of research evaporated after LSD was scheduled worldwide. Aim: The present clinical study is the first to revisit the potential of LSD as an analgesic, and at dose levels which are not expected to produce profound mind-altering effects. Methods: Twenty-four healthy volunteers received single doses of 5, 10 and 20 µg LSD as well as placebo on separate occasions. A Cold Pressor Test was administered at 1.5 and 5 h after treatment administration to assess pain tolerance to experimentally evoked pain. Ratings of dissociation and psychiatric symptoms as well as assessments of vital signs were included to monitor mental status as well as safety during treatments. Results: LSD 20 µg significantly increased the time that participants were able to tolerate exposure to cold (3°C) water and decreased their subjective levels of experienced pain and unpleasantness. LSD elevated mean blood pressure within the normal range and slightly increased ratings of dissociation, anxiety and somatization. Conclusion: The present study provides evidence of a protracted analgesic effect of LSD at a dose that is low enough to avoid a psychedelic experience. The present data warrant further research into the analgesic effects of low doses of LSD in patient populations.